The Effectiveness of TED-ED Video in Improving the Students’ Speaking Skills of Narrative Text - Mosleh, Nejlania; Trisusana, Anis (Applied Research on English Education (AREE), 2024)
The researcher's purpose in conducting this study is to find out whether there is a substantial difference in students' speaking skills in narrative text after the provision of learning using TED-Ed video as learning media for grade 8 students in one of the junior high schools in Gresik. The method used was quantitative experimental, which applied a pretest-posttest research design. There were two classes in this study, namely class VIII F as the experimental class with 32 students and class VIII G as the control class with 32 students. The teaching process in the control class used textbooks as media, while in the experimental class, TED-Ed videos. The research instrument used was a speaking skill test. The researcher used the Independent Sample T-test in SPSS 27 to analyze the results. The results showed that the significant value was .000, less than the significant level of 0.05. Therefore, it indicates a difference between the student's pretest and posttest scores. Then, to show the particular considerable value of the experimental class, the researcher calculated the effect size, whose value was 0.767, which means that the treatment that was given successfully significantly affected the experimental class. The use of TED-Ed videos as learning media for grade VIII students in one of the Junior High Schools in Gresik affected their grades in speaking skills on narrative text.